Sovereignty and the politics of identity in international relations - Kuah, Adrian W. J. (2009)
This paper examines the linkages between the norms and practices of sovereignty and the discourses on the formation of political identity and communities amidst twenty-first century socio-political and economic transformations. By undertaking a postmodern deconstruction of sovereignty, this paper recognizes sovereignty as a subjective, and hence fallible, social construct. It further contends that sovereignty as an Enlightenment project has become untenable with its promise of a universal solution to spatiotemporal problems. Against the backdrop of globalization, this paper problematizes sovereignty and argues that it is inextricably tied to the politics of identity. It also raises the idea of sovereignty as an analogue of the Enlightenment model of the rational sovereign Man. Enshrined most pre-eminently in the nation-state, sovereignty represents simultaneously the locus and limit of what is regarded as political identity. Furthermore, the norms and practices of sovereignty reflect changes in notions and the foci of identity. This paper attempts and points out that the politics of identity and the politics of sovereignty are mutually constitutive, intersubjective discourse. Finally, this paper states that by persistently defining sovereignty in terms of indivisibility and exclusivity, sovereignty itself is becoming an obstacle to human emacipation.